2016
DOI: 10.1097/aud.0000000000000341
|View full text |Cite
|
Sign up to set email alerts
|

Tinnitus and Sleep Difficulties After Cochlear Implantation

Abstract: Objectives: To estimate and compare the prevalence of and associations between tinnitus and sleep difficulties in a sample of UK adult cochlear implant users and those identified as potential candidates for cochlear implantation. Design:The study was conducted using the UK Biobank resource, a population-based cohort of 40-to 69-year olds. Self-report data on hearing, tinnitus, sleep difficulties, and demographic variables were collected from cochlear implant users (n = 194) and individuals identified as potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 38 publications
5
22
1
Order By: Relevance
“…Present findings are in general agreement with findings on unilateral electric amplification of sound by CI as reported in retrospective studies (11, 2830), reviews (3, 4, 3133), and a growing body of prospective studies [e.g., Ref. (7, 12, 3439)].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Present findings are in general agreement with findings on unilateral electric amplification of sound by CI as reported in retrospective studies (11, 2830), reviews (3, 4, 3133), and a growing body of prospective studies [e.g., Ref. (7, 12, 3439)].…”
Section: Discussionsupporting
confidence: 92%
“…On average, as many as 80% of CI candidates experience tinnitus (3, 4). It was realized early that CIs may reduce tinnitus (5) with several authors reporting on tinnitus reduction (611). However, the opposite, namely, exacerbation of a preexisting tinnitus, or development of tinnitus with CI use has also been observed (7, 12).…”
Section: Introductionmentioning
confidence: 99%
“…Practical guidelines for primary care physicians, physician training and pragmatic implementation strategies are likely to enhance guideline adherence for secondary prevention management. Bidirectional referral mechanisms instituted in China in 2015 could facilitate the provision of preventive therapy by primary care institutions22; this programme however is in the early stages of implementation.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review has suggested that CI use has the potential to alleviate the burden imposed by tinnitus (Ramakers, van Zon, Stegeman, & Grolman, 2015). Epidemiological studies have also found tinnitus-related distress to be lower in CI users than in potential candidates to receive a CI and that the effect on distress is associated with tinnitus being perceived less frequently by CI users (Pierzycki et al., 2016).…”
Section: Introductionmentioning
confidence: 99%